Comparing the efficacy of Budesonide and Montelukast in children with asthma: a prospective interventional open label controlled clinical study - Jangam, Sachin S.; Mauskar, Anupama (International Journal of Contemporary Pediatrics, 2017)
Background: Bronchial asthma is a chronic inflammatory airway disease and is more prevalent in children. Inhaled corticosteroids (Budesonide) and leukotriene receptor antagonist (Montelukast) are the drugs of choice for asthma in children. The present study was aimed to compare the efficacy of these drugs in childhood asthma at tertiary care center. Methods: This is a prospective interventional open label controlled clinical study carried out from January 2012 to December 2014. Children recently diagnosed with mild persistent asthma that attended Asthma clinic or admitted in ward of department of paediatrics LTMMC and Hospital, Sion, Mumbai was participated in the study. A total of 70 patients were selected for the study and are categorized into two groups consisting of 35 in each group. Group A patients were given metered dose inhaler (MDI) Budesonide 200 mcg 1 puff twice a day (with MDI spacer and mask for children <5 years and without mask for children >5 years. Group B patients were given Montelukast 4 mg (<5 years) and 5 mg (>5 years) tablet as once a daily in the evening for 1 year. Primary and secondary outcome measures were calculated and analysed. Results: No significant difference on the basis of age and gender was observed among both groups. The complaints of cough, wheeze and breathlessness, lesser emergency department visits, nebulization and lesser number of systemic steroids (days/year) was significantly lesser in patients of group A (p<0.05) compared to group B. Group A subjects had lesser number of acute exacerbations, required lesser number of systemic steroids courses and the frequency of hospitalization. Statistically significant (p<0.05) difference was observed in episode free days in a year among both groups. Conclusions: The findings of the study prove that Budesonide had better efficacy over Montelukast in control of asthma.